Implementasi Steganography Pada Audio Menggunakan Algoritma End of File (EoF) - Angga Aditya Permana (FORMAT, 2020)
Steganography is the art and science of writing hidden messages or hiding messages in a way so that apart from the sender and the recipient no one knows or is aware that there is a secret message. The message is hidden into a media that is audio. One of the methods used in hiding information into audio is the End of File (EOF) method. The purpose of this study is to implement the EOF method to insert messages into audio files. The EOF method works by adding message decimal values to audio files